2013
DOI: 10.1186/1471-244x-13-254
|View full text |Cite
|
Sign up to set email alerts
|

Detection of malingering: psychometric evaluation of the Chinese version of the structured interview of reported symptoms-2

Abstract: Background: Malingering detection has emerged as an important issue in clinical and forensic settings. The Structured Interview of Reported Symptoms-2 (SIRS-2) was designed to assess the feigned symptoms in both clinical and non-clinical subjects. The aim of the study was to examine the reliability and validity of the Chinese version of this scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Of the 45 articles and dissertations examined, three peer reviewed articles each reported the findings of two separate, but related, studies (Liu et al, 2013; Merten, Bossink, & Schmand, 2007; Vossler-Thies, Stevens, Engel, & Licha, 2013). Therefore, a total of 48 studies were examined.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 45 articles and dissertations examined, three peer reviewed articles each reported the findings of two separate, but related, studies (Liu et al, 2013; Merten, Bossink, & Schmand, 2007; Vossler-Thies, Stevens, Engel, & Licha, 2013). Therefore, a total of 48 studies were examined.…”
Section: Resultsmentioning
confidence: 99%
“…Such instruments do have empirical support for their ability to detect malingering (e.g. Vitacco et al, 2008;Hawes & Boccaccini, 2009;Iverson and Lange, 2006;Liu et al, 2013). In a review of a sample of American forensic practitioners, the MMPi-2 and the SIRS were suggested to be the most effective instruments for the detection of malingering (Lally, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Using a three‐step decision model, the examinees are classified into one of the following categories: feigning, intermediate‐evaluate, intermediate‐general, disengagement, and genuine responding (Rogers et al, ). The Chinese version of the SIRS‐2 was available for research purposes (Liu et al, ). A strict translation procedure, which included forward (English to Chinese) and backward (Chinese to English) translation, was implemented.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, criterion‐related validity was examined by using known‐groups comparisons, and there were satisfactory effect sizes of the primary scales for group differences. The sensitivity and specificity were 0.85 and 1.00, respectively, for the sample of known‐groups comparisons (Liu et al, ). Generally speaking, the psychometric properties of the Chinese SIRS‐2 were compatible with the English version.…”
Section: Methodsmentioning
confidence: 99%